2017
DOI: 10.1039/c6cc07403k
|View full text |Cite|
|
Sign up to set email alerts
|

Colloidal atomic layer deposition growth of PbS/CdS core/shell quantum dots

Abstract: Traditionally, PbS/CdS quantum dots (QDs) have been synthesized via a cation exchange method, making fine control over shell growth challenging. We show here that colloidal atomic layer deposition (c-ALD) allows for the sequential growth of single monolayers of the shell, thus creating a 'true' CdS shell on PbS QDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 20 publications
0
39
0
Order By: Relevance
“…This suggests that the fluorescence quenching is mainly induced by the incorporated defects at the PbS/CdS interface during the c-ALD process. Bawendi et al 95 reported similar results with c-ALD growth of CdS shells on PbS QDs. Interestingly, they found the QY of PbS/CdS QDs can be retained by the addition of excessive Cd(OA) 2 at the end of the growth.…”
Section: Synthesis and Properties Of Pbs-based Qdsmentioning
confidence: 52%
“…This suggests that the fluorescence quenching is mainly induced by the incorporated defects at the PbS/CdS interface during the c-ALD process. Bawendi et al 95 reported similar results with c-ALD growth of CdS shells on PbS QDs. Interestingly, they found the QY of PbS/CdS QDs can be retained by the addition of excessive Cd(OA) 2 at the end of the growth.…”
Section: Synthesis and Properties Of Pbs-based Qdsmentioning
confidence: 52%
“…As shown in Fig.6, there are two approaches to form core/shell structure including the cationic exchange and epitaxial shell growth. [102,103] The coated shell may exist in three cases such as uniform shell, composition gradient shell or alloyed shell. Cationic exchange is the most common method to form the shell for PbX QDs because the Pb 2+ cations near the surface are susceptible to be exchanged with other metal ions in the solution such as Cd 2+ cations, which could be proved by the blue-shifted emission of resulted core/shell QDs compared to that of core-only QDs due to the reduced size of PbX QD.…”
Section: Core/shell Structurementioning
confidence: 99%
“…Colloidal atomic layer deposition is a self-limiting layer by layer growth method that has been developed to deposit CdS layers on PbS QDs to produce high-quality PbS/ CdS core-shell QDs. 75 This method allows for fine control of the CdS thickness, down to the monolayer, combined with room temperature conditions. 75 This method could in principle be extended to the synthesis of other QDs system, such as PbSe/CdSe, PbS/CdS/ZnS, HgSe/CdS, etc.…”
Section: Synthesis Of Core-shell Qdsmentioning
confidence: 99%
“…75 This method allows for fine control of the CdS thickness, down to the monolayer, combined with room temperature conditions. 75 This method could in principle be extended to the synthesis of other QDs system, such as PbSe/CdSe, PbS/CdS/ZnS, HgSe/CdS, etc. 75…”
Section: Synthesis Of Core-shell Qdsmentioning
confidence: 99%
See 1 more Smart Citation